2007
DOI: 10.1074/jbc.m608307200
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of JNK-dependent Pathway Is Required for HIV Viral Protein R-induced Apoptosis in Human Monocytic Cells

Abstract: Human immunodeficiency virus (HIV) accessory protein viral protein R (Vpr) plays a key role in virus replication and induces cell cycle arrest and apoptosis in various cell types including T cells and neuronal and tumor cells following infection withApoptosis is an active process mediated by programmed signaling pathways that can be initiated by a variety of intracellular and extracellular stimuli. Apoptosis is essential to many biological processes including functional self-organizational processes in the imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Isolation of Monocytes-Monocytes were purified from PBMCs by negative selection as described earlier (16,35). Briefly, PBMCs were incubated with magnetic polystyrene Dynabeads (Dynal Biotech, Oslo, Norway) coated with anti-CD2 (T cells) and anti-CD19 (B cells) antibodies for 30 min on ice for depletion of T and B cells, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of Monocytes-Monocytes were purified from PBMCs by negative selection as described earlier (16,35). Briefly, PBMCs were incubated with magnetic polystyrene Dynabeads (Dynal Biotech, Oslo, Norway) coated with anti-CD2 (T cells) and anti-CD19 (B cells) antibodies for 30 min on ice for depletion of T and B cells, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Induction of survivin expression by Vpr may then delay HIV-induced mitochondrial dependent apoptosis. This effect may be cell-type dependent, since Vpr expression in monocytes downregulates the expression of another member of the IAP family, c-IAP1, possibly contributing to Vpr’s pro-apoptotic effects [39]. …”
Section: Late Events In the Hiv Virus Life Cyclementioning
confidence: 99%
“…Using macrophage-like cells derived from differentiated THP1 CD4+ myeloid cells, a recent report showed that Vpr is not able to downregulate the anti-apoptotic protein cIAP1/2 (Busca et al, 2012). However, Mishra et al (2007) previously revealed the possibility that the C-terminal part of Vpr could induce apoptosis in monocytes via a JNK-dependant pathway.…”
Section: Vpr and Apoptosismentioning
confidence: 99%